Logika, Penalaran, Dan Argumentasi Hukum - Wiranto Wiranto; Mozes lawolata (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
Nowdays, the understanding and knowledge in logic, reasoning, and legal argumentation become moreabsolute necessity not only for civitas academica in philosophy and law but most important for legal practitioners as polices, judges, prosecutors, attorneys, lawyers, and even all members of society whosedealing with legal problems everyday. As apart of generally reasoning, legal reasoning, although have some different characteristics, is attached to valid principles of reasoning such as rules of reasoning, rules of sillogism, rules of inductive probability, and informal fallacies. Thus legal reasoning is not a distinct and separate kind of reasoning from logic as science of how to think rightly, appropriately, and valid (as a branch of philosophy) but rather how to applied rules of reasoning from logic principles to legal problems. This article explores the rules of thinking in induction and sillogism. IRAC (Issue, Rule, Argument, dan Conclusion) model as an application of inductive and sillogistic reasoning in law will to end this article.